INOVASI PELAYANAN E-SIAP (ELEKTRONIK SISTEM APLIKASI PENDAFTARAN) DALAM PENINGKATAN KUALITAS PELAYANAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BLITAR - Lisa Ardelia; Galih Wahyu Pradana (Universitas Negeri Surabaya, 2022)
Electronic Registration Application System (E-SIAP) is an innovation presented by the Department of Population and Civil Registration of Blitar Regency, this innovation is presented with the overcoming the problem where queues are always booming every day and make it easier for the public to manage population documents without having to come to the office. With innovation, it can increase efficiency and effectiveness in service delivery. In this way the level of community satisfaction can increase. The purpose of study is to describe and analyze the implementation of the E-SIAP innovation. This research use desciptive qualitative approach. Data collection techniques consist of observation, interviews, and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the study indicate that the E-SIAP innovation has been running well according to the direction of the Director General of Civil Registration of the Ministry of Home Affairs, which has declared go-digital and the Population Administration Law. The source of innovation ideas is obtained from the the community and the government of the Dispendukcapil Regency of Blitar Regency. There are still some people who take care of the innovation culture manually, namely those who do not have proper access. The capabilities and tools contained in the E-SIAP innovation can support the smooth delivery of services to the community. The goals and results are considered good by facilitating service. Then there is a good response from the community and the most basic obstacle is that there are still several generations who are not technology literate. In collecting innovation data for a single innovation, the Dispendukcapil does not only involve internal organizations but also stakeholders such as collaborating with all villages in Blitar Regency with Salam Sak Jangkah. Keywords: Service Innovation, E-SIAP, service quality.